Screening for Antimicrobial Activities in Soil Microbes Isolated From Nanga Merit Site 2 - Chai, Sin Lin (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was carried out on soil samples collected from Nanga Merit forest (Site 2) in the efforts to discover novel antibiotics produced by soil microbes. A total of 30 bacterial and 38 fungal isolates were successfully selected and colony purified. Antibiotic activity screening by using agar overlay technique followed by secondary screening have obtained one bacterial isolate (B17) and four fungal isolates (F10, F11, F14, and F26) thatshowed strong antibacterial activity against different strains of test bacteria. These test bacteria were Staphylococcus aureus, Salmonella typhi, Escherichia coli, and Enterobacter aerogenes. Some synergistic effects were showed by fungal isolates (F2, F5, F17, F18, F20, and F21) grown on CDA when tested against S. aureus, E. coli, and E. aerogenes. Only one bacterial isolate (B17) and 12 fungal isolates (F2, F3, F5, F17, F18, F20, F21, F10, F11, F14, and F26) were selected for further antibiotics susceptibility testing and characterisation. Selected fungal isolates were cultivated on three types of culture media (PDA, CDA, and V8 Juice Agar). Only one extract (B17) was selected for MIC value determination. The potential of B17 to be further studied was showed by the small MIC value (<1.5625 mg/ml) and large inhibition size that was comparable to the positive control (5× dilutions of penicillin-streptomycin solution). Besides, extract of B17 also showed antifungal activity when tested against test fungus (Fusarium sp.). Besides, fungal isolates (F10, F11, F14, and F26) cultivated on PDA were also exhibited good antifungal activities when tested against the same test fungus. B17 was tentatively identified as Phenylobacterium sp. based on their physical appearances and biochemical tests results. Among the 11 fungi which were subjected to characterisation, seven isolates (F2, F3, F5, F17, F18, F20, F21, F10, F11, F14, and F26) and four isolates (F10, F11, F14, and F26) were tentatively identified as Penicillium spp. and Streptomyces spp., respectively. Further tests will be needed in order to determine the exact identity of these isolates.